Motor Exit Point (MEP) Glia: Novel Myelinating Glia That Bridge CNS and PNS Myelin - Fontenas, Laura; Kucenas, Sarah (Frontiers in Cellular Neuroscience, 2018)
Oligodendrocytes and Schwann cells have traditionally been thought of as the exclusive myelinating glial cells of the central and peripheral nervous systems, respectively, for a little over a century. However, recent studies demonstrate the existence of a novel, centrally-derived peripheral glial population called motor exit point (MEP) glia, which myelinate spinal motor root axons in the periphery. Until recently, the boundaries that exist between the central and peripheral nervous systems, and the cells permitted to cross them, were mostly described based on fixed histological collections and static lineage tracing. Recent work in zebrafish using in vivo, time-lapse imaging has shed light on glial cell interactions at the MEP transition zone and reveals a more complex picture of myelination both centrally and peripherally.